PCR TESTING FOR SARS-COV-2: PRACTICE, RECCOMMENDATIONS AND DILEMMAS - Popadic, Dusan (HEALTH CARE, 2020)
In the Covid-19 pandemic, diagnostic laboratories have met multiple new demands, which have gone beyond the existing personnel, technical and material capacities. According to the current recommendations, the base of laboratory diagnostics for Covid-19 is a Real-Time Reverse Transcription Polymerase Chain Reaction (rtRT-PCR) test, which detects the presence of SARS-CoV-2 genome in the biological material collected from the patient. The procedure of testing can conditionally be divided into several stages: 1) setting the indications for testing; 2) collecting the clinical samples and filling in the documentation; 3) transport of the material to the diagnostic laboratory; 4) reception and classification of the material; 5) the analysis of samples after the reception – the preparation for rtRT-PCR; 6) rtRT-PCR; 7) communicating results. It is clear that medical microbiological services have not been standardized for the fight against the pandemic or great epidemics. The most efficient way to overcome such a situation is to define teams, which would take part in the diagnostics, when the epidemiological situation demanded it. It is necessary to strive to have the unified equipment on the whole territory of The Republic of Serbia, because in that way the maintenance and procurement of spare parts and consumables are made easier, and the purchasing price could possibly be lowered. Reagents for the extraction and specific reagents for rtRT-PCR (primers and probes) should be standardized and made in Serbia in order to decrease the dependence on imports and make significant money savings. The database of laboratory results should be improved and organized according to the FAIR (findability, accessibility, interoperability, and reusability) principles in order to use the possibility of making conclusions maximally.